Effect of Application of Natural Polyphenol Containing Polymer Coatings on Quality of Pork Balls - Rao, V. Giridhara; Mallika, E. Naga; Rao, B. Eswara (Journal of Meat Science, 2019)
An attempt was made to evaluate the quality of pork balls coated with starch (T1), starch incorporated with 1% Tannic acid (T2), and starch incorporated with 1% Quercetin (T3) and were analyzed at regular intervals of 5 days and 15 days under refrigeration (4 ± 1OC) and frozen storage temperatures (-18 ± 1OC) respectively. The values of pH, TBA, PV, TPC and per cent water loss of the coated pork balls increased significantly (P<0.05) during the storage period for all the treatment groups, but the rate of increase was at a lower level in natural polyphenols incorporated formulations when compared to control and starch coated ones. They were well acceptable up to 15 days under refrigerated storage and up to 75 days under frozen temperature. The polyphenol enriched starch coated products showed significantly (P<0.05) lower total plate counts when compared to non coated control irrespective of type of polyphenols incorporated. The coatings were tested for their antimicrobial ability against various antibiotics by disc diffusion method. The zone of inhibition was significantly higher for 1% Tannic acid 1% quercetin incorporated starch coatings when compared to the control. The present study demonstrated that tannic acid and quercetin can be successfully incorporated into biodegradable starch coatings and films and can exhibit excellent antioxidant and antimicrobial activities as a part of active packaging, to extend the shelf life of the product.